2007
DOI: 10.1053/j.gastro.2007.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte–Colony Stimulating Factor Promotes Liver Repair and Induces Oval Cell Migration and Proliferation in Rats

Abstract: Background & Aims-Hepatic regeneration is a heterogeneous phenomenon involving several cell populations. Oval cells are considered liver stem cells, a portion of which derive from bone marrow (BM). Recent studies have shown that granulocyte-colony stimulating factor (G-CSF) may be effective in facilitating liver repair. However, it remains unclear if G-CSF acts by mobilizing BM cells, or if it acts locally within the liver microenvironment to facilitate the endogenous restoration program. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 29 publications
3
102
1
1
Order By: Relevance
“…What needs to be mentioned is that in Kupffer cells, CSF-mediated signaling pathways including Ras/Raf/Mapk, Pi3k/Akt and Jak/Stat became inactive during the whole LR. According to previous studies, CSF could improve liver repair and restoration, implicating the relative active signal pathway triggered by them (Piscaglia et al, 2007). However, the difference between our results and those of other studies suggests the possibility that the inactive CSF-mediated signaling pathways during LR may be try to prevent the regenerating liver from inflammatory injury caused by CSF, or this difference is related to the difference between tissue-level studies and cell-level studies.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…What needs to be mentioned is that in Kupffer cells, CSF-mediated signaling pathways including Ras/Raf/Mapk, Pi3k/Akt and Jak/Stat became inactive during the whole LR. According to previous studies, CSF could improve liver repair and restoration, implicating the relative active signal pathway triggered by them (Piscaglia et al, 2007). However, the difference between our results and those of other studies suggests the possibility that the inactive CSF-mediated signaling pathways during LR may be try to prevent the regenerating liver from inflammatory injury caused by CSF, or this difference is related to the difference between tissue-level studies and cell-level studies.…”
Section: Discussioncontrasting
confidence: 81%
“…As previously stated, the postoperative administration of CSF1, 2 or 3 promotes the proliferation of hepatic cells by inducing intracellular cascades, thus contributing to liver regeneration (Kaushansky, 2006;Akagawa et al, 2006;Piscaglia et al, 2007). To clarify how CSF impact the regeneration process at the cellular level, we performed high throughput analysis to measure expression profiles of CSF-mediated signaling pathway genes in eight hepatic cell types following PH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transplanted oval cells can make a modest (∼2% after 1 month, falling to 0.4% at 6 months) contribution to the hepatocyte population in the CCl 4 -damaged mouse liver [92]. The progenitor response can be manipulated in vivo; in the 2-AAF/PH model the oval cell reaction can be significantly boosted by G-CSF [93], and a small study of patients with alcoholic steatohepatitis found that 5 days of G-CSF treatment resulted in a four-fold increase in proliferating HPCs [94].…”
Section: The Facultative Stem Cell Response: Oval/hepatic Progenitor mentioning
confidence: 99%